2008
DOI: 10.1016/j.physletb.2008.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Parametrization of Bose–Einstein correlations and reconstruction of the space–time evolution of pion production in e+e− annihilation

Abstract: A parametrization of the Bose-Einstein correlation function of pairs of identical pions produced in hadronic e + e − annihilation is proposed within the framework of a model (the τ -model) in which space-time and momentum space are very strongly correlated. Using information from the Bose-Einstein correlations as well as from single-pion spectra, it is then possible to reconstruct the space-time evolution of pion production. ‡ Present address:

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…In this model the simple Q dependence is a consequence of a strong correlation between a particle's fourmomentum and its space-time point of production. This strong correlation also leads to a decrease of the observed source size with increasing m t [24].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…In this model the simple Q dependence is a consequence of a strong correlation between a particle's fourmomentum and its space-time point of production. This strong correlation also leads to a decrease of the observed source size with increasing m t [24].…”
Section: Introductionmentioning
confidence: 78%
“…Then the two-particle Bose-Einstein correlation function is indeed found to depend on the invariant relative momentum Q, rather than on its separate components, as well as on the values of a of the two particles [24]:…”
Section: The τ -Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…We have recently published [1] a study of Bose-Einstein correlations (BEC) in hadronic Z decay where we found good agreement with parametrizations arising in the τ -model [2,3].…”
Section: Introductionmentioning
confidence: 74%
“…We choose a one-sided Lévy distribution, which is characterized by three parameters: the index of stability α, the proper time of the start of particle emission τ 0 , and ∆τ , which is a measure of the width of H(τ ). Then [13] …”
Section: Parametrizations Of Becmentioning
confidence: 99%